The Service quality, corporate image, satisfaction, and loyalty: A study of Sharia banks in rural areas during COVID-19 - Haryanto, Rudy; Al Jufri, Elda Ayu Nabila; Ahmad, Azline Alisa (Universitas Negeri Surabaya, 2023)
This research investigates the relationship between customer satisfaction and loyalty in a rural Sharia bank in Indonesia during the post-pandemic period. The study seeks to understand how the pandemic has affected customers' perceptions and loyalty and analyse the impact of corporate image on customers’ loyalty. The research method used regression analysis and path analysis. The results reveal the positive and significant effects of service quality and corporate image on customers' satisfaction, indicating the importance of these factors in maintaining customer contentment during challenging times. However, the quality of service and the corporate image do not influence customers’ loyalty. This research provides valuable insights for Islamic banks and other financial institutions in enhancing customer loyalty strategies. By prioritising service quality and cultivating a positive corporate image, banks can foster more significant levels of customer satisfaction, ultimately leading to increased customer loyalty and a strengthened competitive advantage.